Improving PAI Learning Outcomes by Using the Symposium Discussion Method at SMAN 1 Suliki - Al Andika Surya Wipama (BiCED Proceeding, 2024)
This research aims to improve students' learning outcomes through questioning skills in the Islamic Religious Education learning process using the symposium discussion method. The study was conducted in class X E 1 SMAN 1 Suliki in two cycles, focusing on enhancing the quality of learning and developing students' questioning skills. Data was collected through observation, tests, and interviews with the teacher. The results showed a significant improvement in students' learning outcomes, with students achieving a "good" grade category increasing to 73.33% in the second cycle. The implementation of the symposium discussion method successfully improved students' questioning skills, enriched their learning experiences, and enhanced their understanding of the material. This study concludes that the symposium discussion method is effective in improving the learning outcomes of Islamic Religious Education in class X E 1 SMAN 1 Suliki.